2012
DOI: 10.1186/1742-4690-9-52
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase PPM1A negatively regulates P-TEFb function in resting CD4+ T cells and inhibits HIV-1 gene expression

Abstract: BackgroundProcessive elongation of the integrated HIV-1 provirus is dependent on recruitment of P-TEFb by the viral Tat protein to the viral TAR RNA element. P-TEFb kinase activity requires phosphorylation of Thr186 in the T-loop of the CDK9 subunit. In resting CD4+T cells, low levels of T-loop phosphorylated CDK9 are found, which increase significantly upon activation. This suggests that the phosphorylation status of the T-loop is actively regulated through the concerted actions of cellular proteins such as S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…CDK9 phosphorylation at the conserved T-loop residue Thr186 is inducible in quiescent CD4 + T lymphocytes, but is found to be constitutive in actively replicating T cell lines and expanding, fully activated, T cells (34)(35)(36)62,63). Consistent with molecular dynamics simulations, cell-based mutagenesis experiments demonstrated that the assembly of P-TEFb in T cells is critically dependent on the stabilization of the CDK9/CycT1 interface by phosphorylation of CDK9 at Thr186.…”
Section: Formation Of the Heterodimer Interface Between Cdk9 And Cyctmentioning
confidence: 63%
See 2 more Smart Citations
“…CDK9 phosphorylation at the conserved T-loop residue Thr186 is inducible in quiescent CD4 + T lymphocytes, but is found to be constitutive in actively replicating T cell lines and expanding, fully activated, T cells (34)(35)(36)62,63). Consistent with molecular dynamics simulations, cell-based mutagenesis experiments demonstrated that the assembly of P-TEFb in T cells is critically dependent on the stabilization of the CDK9/CycT1 interface by phosphorylation of CDK9 at Thr186.…”
Section: Formation Of the Heterodimer Interface Between Cdk9 And Cyctmentioning
confidence: 63%
“…However, the data on their role in HIV transcription has been somewhat contradictory. Rice and colleagues (62) found that the siRNA knockdown of PPM1A expression in HIV-infected resting CD4 + T cells increased the level of CDK9 Thr186 phosphorylation in the absence of T-cell stimulation, and this was coupled with enhanced HIV gene expression. By contrast, Ammosova et al (76) reported that the stable expression of a peptide-based inhibitor of PP1, cdNIPP1, promoted CDK9 Thr186 phosphorylation.…”
Section: Formation Of the Heterodimer Interface Between Cdk9 And Cyctmentioning
confidence: 98%
See 1 more Smart Citation
“…ϩ T cells (29). It is probable that PPM1A is involved in dephosphorylating the T loop in naïve cells and quiescent memory CD4 ϩ T cells.…”
Section: Fig 6 In Resting Cd4mentioning
confidence: 99%
“…While the total levels of CDK9 remain relatively constant through resting versus activated states, the levels of T-loop-phosphorylated CDK9 (pCDK9) are very low in resting CD4 ϩ T cells due to the action of the phosphatase PPM1A (29,30). However, activation of these cells induces phosphorylation of the CDK9 T loop by an activating kinase that has recently been shown to be CDK7 (31).…”
mentioning
confidence: 99%